2013
DOI: 10.1134/s1068162013030114
|View full text |Cite
|
Sign up to set email alerts
|

Unique structural organization of ATP-dependent LonA proteases

Abstract: Homooligomeric LonA proteases are the key components of the protein quality control system in bacteria and eukaryotes. Domain organization of the common pool of LonA proteases is determined by comparative analysis of primary and secondary structures of a number of bacterial and eukaryotic enzymes. The similarity of individual enzyme domains was estimated, domain-domain linker areas were revealed, regions that are capable to include intercalated peptide fragments were identified. LonA proteases were shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Whereas a resemblance of the HI(CC) domain of LonA to the H1(M) fragment of ClpB has been previously suggested , no structural basis for such a topological similarity has been established. A comparison of the primary and secondary structures of the HI(CC) domains of Ec Lon, Bs Lon, and Mt Lon on the one hand, and the H1(M) fragments of E. coli and Thermus thermophilus ClpB chaperones ( Ec ClpB and Tt ClpB) on the other hand (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Whereas a resemblance of the HI(CC) domain of LonA to the H1(M) fragment of ClpB has been previously suggested , no structural basis for such a topological similarity has been established. A comparison of the primary and secondary structures of the HI(CC) domains of Ec Lon, Bs Lon, and Mt Lon on the one hand, and the H1(M) fragments of E. coli and Thermus thermophilus ClpB chaperones ( Ec ClpB and Tt ClpB) on the other hand (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Structural data are available for two N‐terminal fragments of Ec Lon, consisting of 116 and 245 amino acid residues, respectively , as well as for a fragment of Bs Lon (1–209) . These structures, combined with prediction of the secondary structures for several other LonA proteases (http://www.ch.embnet.org), revealed that the extended N‐terminal region of LonA proteases preceding the AAA + module is formed by two domains, the predominantly β‐structured N domain, and the α‐helical HI(CC) domain (Figs and ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations